Vehicle-to-Home: Implementation and Design of an Intelligent Home Energy Management System that uses Renewable Energy - Alkhudhayr, Hanadi; Subahi, Alanoud (Engineering, Technology & Applied Science Research, 2024)
Using energy storage technology, such as batteries and electric vehicles, is crucial in combating energy shortages. Wind turbines and solar panels are two prominent alternative energy sources. This study examines the impact of Vehicle-to-Home (V2H) technology, specifically during the hours when solar radiation is at its highest. V2H enables electric car batteries to be a primary solution for home energy needs. An accurate scheduling system has been established to improve the organization's energy sustainability. The proposed algorithm effectively controls the allocation, availability, and retention of energy transported by electric vehicles (EVs). The model incorporates constraints to ensure that the family's electricity needs are met regardless of the prevailing weather conditions, whether sunny or cloudy. The Intelligent Home Energy Management System (IHEMS) is being developed to regulate energy use efficiently across different applications and sources. A multi-agent system (MAS) is used to improve operational efficiency and effectively meet the energy needs of devices in the system. An experimental database in Saudi Arabia examines and monitors production costs and energy consumption, considering weather conditions and equipment utilization. The results demonstrate the great potential of V2H technology as a practical storage option that efficiently addresses energy shortages.